2012
DOI: 10.1016/j.micinf.2012.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Role of extracellular nucleotides in the immune response against intracellular bacteria and protozoan parasites

Abstract: Extracellular nucleotides are danger signals involved in recognition and control of intracellular pathogens. They are an important component of the innate immune response against intracellular pathogens, inducing the recruitment of inflammatory cells, stimulating secretion of cytokines, and producing inflammatory mediators such as reactive oxygen species (ROS) and nitric oxide (NO). In the case of extracellular ATP, some of the immune responses are mediated through activation of the NLRP3 inflammasome and secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 79 publications
(85 reference statements)
3
77
0
1
Order By: Relevance
“…Bars represent the mean ± standard error of the mean of three independent experiments performed with three animals. *p < 0.05; **p < 0.01 using Student's t test and one-way ANOVA coupled to Tukey's post hoc test comparing infected P2X7 KO and WT mice at the same timepoint [13,24,25]. The role of the P2X7 receptor in a wide range of infectious diseases has been studied in vitro and in vivo using P2X7 KO mice [10,26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bars represent the mean ± standard error of the mean of three independent experiments performed with three animals. *p < 0.05; **p < 0.01 using Student's t test and one-way ANOVA coupled to Tukey's post hoc test comparing infected P2X7 KO and WT mice at the same timepoint [13,24,25]. The role of the P2X7 receptor in a wide range of infectious diseases has been studied in vitro and in vivo using P2X7 KO mice [10,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…P2X7 receptor stimulation leads to the activation of multiple immune signalling pathways, including the MyD88/NFκB pathway and the phospholipase D pathway [12]. In addition, this receptor induces ROS production and apoptosis, mechanisms that have important anti-pathogenic roles [13]. ATP also rapidly induces autophagy in human and mouse macrophages, resulting in mycobacterial killing in a process dependent on Ca ++ influx [14].…”
Section: Introductionmentioning
confidence: 99%
“…The role of ATPe during protozoan infection has also been studied. It has been demonstrated that the P2X7 receptor participates in the elimination of many intracellular parasites (26). The role of the P2X7 receptor via ATPe has been demonstrated in Toxoplasma gondii infection.…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evidence implicates P2XR during inflammation and immune response against microbes 72,78 . Although several other P2XRs are functional during inflammation (for example, P2X 4 R), P2X 7 R in particular has been shown to affect the outcomes of inflammatory or infectious diseases.…”
Section: P2xr Signalling During Inflammationmentioning
confidence: 99%